GIRIREJO VILLAGE MICRO SMALL AND MEDIUM ENTERPRISES EMPOWERMENT MODEL THROUGH THE WIRADESA ROGRAM - Ahmad Nur Rohim; Shaffira Ayuning Byzhura; Dewi Anggraeni Sekarwati (Universitas Islam Indonesia, 2021)
Background: The Village Sustainable Development Goals (SDGs) are an integrated effort that includes 18 development goals in solving village’s problems. The SDGs are a real effort to accelerate sustainable development at the village level to create villages without poverty, hunger, and equitable national economic growth. One way to achieve this is by building empowered rural micro small and medium enterprises. Therefore, it is necessary to analyze the micro small and medium enterprises empowerment program to train village entrepreneurs to develop their businesses in a sustainable manner. This study aims to determine the right empowerment program to be applied to micro small and medium enterprises and identify stakeholders who help implement the program. Method: Determination of the research area using a purposive method, namely village owned enterprises and meatball home industry in Girirejo Village, Imogiri, Bantul, D.I.Y. The sampling method was carried out by purposive sampling using certain criteria. The data used are primary and secondary data using data collection methods in the form of observation, interviews, and documentation. Result: The results show that the empowerment programs that needed by micro, small and medium enterprises include production and operations management training, supply chain management training, digital marketing training, production and product development training, and marketing management training. Conclusion: This empowerment program optimizes and develops existing MSMEs in Girirejo Village for the better, the scope of this program is to increase the capacity of human resources and business capacity. Keywords: SDGs, Empowerment, micro small and medium enterprises